ANALISIS KETERAMPILAN BERBICARA PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SEKOLAH DASAR - Handayani, Nurul Rika; Magdalena, Ina; Fadhillah, Dilla (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to describe the speaking skills of fourth grade elementary school students. This research uses descriptive research methods with a qualitative approach. Sources of research data are school principals, teachers, students and guardians of SD Negeri Buaran Bambu IV, Tangerang Regency. Data collection techniques in this research used observation, performance tests, and interviews. The data analysis technique in this research uses data reduction, data presentation, and drawing conclusions. The results of this study showed that there were 5 students who got A grades, 12 students got B grades, 2 students got C grades, and 3 students got D grades in speaking skills using performance tests.